Simultaneous Determination of Six Ingredients in Wenweishu Capsule by RP-HPLC - Zhong, Ningyuan; Gao, Jie; Cheng, Weiming; Chai, Jun; Yue, Chao; Zhang, Wenting (Asian Journal of Chemistry, 2014)
This study established the HPLC method for the simultaneous determination of six ingredients in Wenweishu capsule. The sample was extracted with methanol by ultrasonication. The HPLC separation was performed on a zorbax SB-C18 (4.6 × 250 mm, 5 μm) column, using acetonitrile (A)-0.1 % formic acid (B) as the mobile phase with gradient elution in a flow of 1 mL min-1. The column temperature was at 30 °C and the detector wavelength was 330 nm. The results showed that the six components were separated well and had good linear relationships: Calycosin glycoside in the range of 0.1012-2.024 μg (R2 = 0.9997); Echinacoside in the range of 0.01974-0.3984 μg (R2 = 0.9998); Verbascoside in the range of 0.01067-0.2134 μg (R2 = 0.9996); Chlorogenic acid in the range of 0.02014-0.4028 μg (R2 = 0.9994); Vitexin rhamnoside in the range of 0.02250-0.4500 μg (R2 = 0.9993) and hesperidin in the range of 0.009440-0.1888 μg (R2 = 1.0000) (n = 6). Their average recoveries were between 95-105 % (n = 6). This method was steady with high precision and good repeatability and non-interference in the negative control. It could be used for the determination of the six active ingredients and quality control of Wenweishu capsule.